2016
DOI: 10.3390/environments4010001
|View full text |Cite
|
Sign up to set email alerts
|

Bioremoval of Phenol from Aqueous Solutions Using Native Caribbean Seaweed

Abstract: Among several Puerto Rican algae, Sargassum sp. (SG) and Chaetomorpha (CM) showed the highest phenol adsorption capacity from aqueous solutions and were used in optimized adsorption batch experiments at room temperature. The effects of pH, adsorbent dose, phenol concentration, salinity and presence of interfering substances were evaluated. Initial solution pH exhibited a strong effect, mainly on the phenol aqueous chemistry; showing the maximum adsorption at pH 10. Sorption isotherm results were modelled accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…However, the adsorption favorability through the value of K L and n in Equations (7) and (9) was also determined. In short, these results were consistent with the model analysis that the adsorption process was mainly derived by chemical mechanism [49].…”
Section: Resultssupporting
confidence: 89%
“…However, the adsorption favorability through the value of K L and n in Equations (7) and (9) was also determined. In short, these results were consistent with the model analysis that the adsorption process was mainly derived by chemical mechanism [49].…”
Section: Resultssupporting
confidence: 89%
“…as well as to study its antioxidant and antitumor activity. A previous study 10 found the major elements found in Chaetomorpha to be carbon and oxygen. Sulfur, potassium, sodium, and chlorine were found in minor amounts.…”
Section: Discussionmentioning
confidence: 91%
“…Sargasso is also efficient in removing organic dyes (e.g., Methylene blue used in the textile, paper, and cosmetic industries), with removal efficiencies of 95-98%. Sargasso has also been used for the removal of phenol from aqueous solutions [111,121,122]. Filters made with sargasso could be used for the treatment of wastewater and its later domestic, agricultural, or industrial use.…”
Section: Biosorption Potential Of Sargasso Biomassmentioning
confidence: 99%